2013
DOI: 10.3389/fpls.2013.00428
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxins are essential for stress adaptation in the cyanobacterium Synechocystis sp. PCC 6803

Abstract: Glutaredoxins are small redox proteins able to reduce disulfides and mixed disulfides between GSH and proteins. Synechocystis sp. PCC 6803 contains three genes coding for glutaredoxins: ssr2061 (grxA) and slr1562 (grxB) code for dithiolic glutaredoxins while slr1846 (grxC) codes for a monothiolic glutaredoxin. We have analyzed the expression of these glutaredoxins in response to different stresses, such as high light, H2O2 and heat shock. Analysis of the mRNA levels showed that grxA is only induced by heat whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 88 publications
2
22
0
Order By: Relevance
“…Some monothiol Grxs have also been reported to catalyze protein deglutathionylation [ 67 ]. The poorly understood cyanobacterial Grxs are studied in Synechocystis PCC6803 because it possesses only three Grxs, which are all are dispensable to cell growth under standard photoautotrophic conditions [ 14 , 68 ]. The dithiol enzymes Grx1 (Slr1562, also known as GrxB) and Grx2 (Ssr2061, also known as GrxA) operate in the tolerance to arsenate [ 54 , 55 ].…”
Section: The Glutaredoxin Enzymes Operate In the Protection Againsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some monothiol Grxs have also been reported to catalyze protein deglutathionylation [ 67 ]. The poorly understood cyanobacterial Grxs are studied in Synechocystis PCC6803 because it possesses only three Grxs, which are all are dispensable to cell growth under standard photoautotrophic conditions [ 14 , 68 ]. The dithiol enzymes Grx1 (Slr1562, also known as GrxB) and Grx2 (Ssr2061, also known as GrxA) operate in the tolerance to arsenate [ 54 , 55 ].…”
Section: The Glutaredoxin Enzymes Operate In the Protection Againsmentioning
confidence: 99%
“…Emphasizing on the crosstalk between the Grx and Trx systems, we found that Grx1 and Grx2 operate in an integrative redox pathway, NAD(P)H-thioredoxin reductase–Grx1–Grx2–ferredoxin 7, which transfer electrons in that order, to reduce selenate [ 60 ]. The Grx2 enzyme also operates in the tolerance to H 2 O 2 [ 60 , 68 ] and heat shock [ 68 ].…”
Section: The Glutaredoxin Enzymes Operate In the Protection Againsmentioning
confidence: 99%
“…The main reason for the slow growth in mutations of Grx2 may be the influence of Fe-S cluster metabolism in the nitrogenase complex assembly ( Benyamina et al, 2013 ). In many organisms, including yeast, Synechocystis , Arabidopsis thaliana , mouse, and human, disruption of Grx caused highly sensitive to stress-induced oxidative damage, indicating that Grx plays an important role in stress adaptation ( Rodríguez-Manzaneque et al, 2002 ; Lillig et al, 2004 ; Chung et al, 2005 ; Cheng, 2008 ; Mühlenhoff et al, 2010 ; Wu et al, 2011 ; Sánchez-Riego et al, 2013 ). In this study, the loss of NcGrx1 caused growth-inhibition of parasites under oxidative stress (H 2 O 2 ) condition, which indicated that NcGrx1 is crucial for maintaining redox balance in N. caninum under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…RpaB seems to regulate most genes of the glutathione/glutaredoxin system, relevant to prevent photooxidative damage. GrxA and GrxC were reported to be the only HL-inducible glutaredoxins, serving as electron acceptors of glutathione (63).…”
Section: Discussionmentioning
confidence: 99%